A instrução para os desfavorecidos da sorte : obrigação ao trabalho no sertão da ignorancia, MG-1889-1909 - Vilela, Claudia Oliveira Cury (2016)
This thesis is the result of an investigation that analyzed the instruction process directed to those that, previously neglected socio-economically, became useful for the urgent promotion of state economy. This study, thus, involves the period in which the Republic of Brazil comes to existence, in 1889 when the state of Minas Gerais faced an economic hardship, worsened by the lack of labor for the crops, mainstay of state finances. The study extends to 1909, when the State organized the Instituto João Pinheiro, with the mission of solving the demand for labor, prioritizing the marginalized, the neglected, the delinquent youngster and the son of proletarian, transforming them into workers. In this perspective, the ideas of instruction at and for work were understood in the light of the state legislation context at the time, characterized as the dawn of Brazilian Republic and of the State of Minas Gerais parliament tribune where we could apprehend that the voices echoed in favor of mandating the disgraced to become occupied and productive, meeting the expectations of the liberal capitalist State-Nation. Therefore, in the direction of political-economical intentions of Minas Gerais, which, in a certain way, mandated that the individual be instructed for and at work, is that the primary sources the Annaes of the State Congress - were listed. Besides this document scope, other sources relevant were relevant: newspapers, maps, reports, and other historic documents searched at the Public Archives of the State of Minas Gerais and other digital archives, besides the state and federal laws. The legal modes proposed by the State as a coercion mode from individual idleness, as well as the distinct instruction loci for the unfortunate ones are, in this study, apprehended as moving proposals that converge to trends and possibilities of forcing individuals, in some way, to maintain their status quo, since it preconized an inequality of opportunities. Beyond these concerns, it was observed that, with the decline of the Imperial Period, the State of Minas Gerais remained faithful and confident of its catholic convictions, closing rows of Catholicism and, defending this belief in a moment in which the State-Nation, officially, proclaimed itself a lay state favored the catholic socio-educational enterprises, bargaining with the Church state properties in exchange for Salesian Christian actions that left their mark on the instruction scenario for the miserable in the state. Understanding about the partnership with the Salesian on the formation of workers that were disciplined, clean and subservient, to put an end to the problem of the unfortunate ones and minimize the state demand for labor, was not an objective, a priori, but was revealed itself as important as the investigation advanced, also conferring uniqueness to this study, indicating that the Salesian mode of instructing the unfortunate for labor the organization of Instituto João Pinheiro.